A Semiotic Analysis of the Political Posters in the 2024 Indonesian’s Presidential Campaign - Panggabean, Nurmayanti Margaret; Pasaribu, Arsen Nahum; Sihite, Jubilezer (Universitas Islam Negeri Palopo, 2025)
This research discusses semiotic analysis of political posters in the 2024 Indonesian Presidential Campaign. This research aims to identify and analyze icons, index, and symbols and find the meaning of their interpretation contained in the poster. This research uses a qualitative descriptive method using the semiotics theory proposed by Charles Sanders Pierce. In this research, the author first selected five posters from each candidate via the internet. Then, the author describes and analyzes the meaning of each sign on the political poster using Pierce's triangle. In this research, the author found the use of 18 icons in 15 data, 41 indexes and 48 symbols. The poster's use of color, layout, and text provide clues about the emotion it is trying to convey to voters, whether it is optimism, confidence, or a call for change. The results of these findings show that symbol signs are the type of sign that the authors found most often in this research.